Improving the Implementation of Advance Directives in Spain. (11th April 2023) - Herreros, Benjamín; Gella, Pablo; Valenti, Emanuele; Márquez, Octavio; Moreno, Beatriz; Velasco, Tayra
Abstract: Since 2002, legislation in Spain has allowed for the creation and documentation of end-of-life decisionmaking. Over the intervening years, the actual implementation of such documents is very low. Through extensive analysis of the literature, this article explores the current status of the use of and attitudes toward advance directives in Spain and then proposes strategies for improvement in their implementation.